A comparative study on strategic analysis and forecasting on profit maximization and operational efficiency in manufacturing business through differential equations: A comparative study on strategic analysis and forecasting on profit maximization and operational efficiency in manufacturing business through differential equations - Jha, Aditya; Suresh, Suresh Kumar Sahani; Jha, Anshuman; Sahani, Kameshwar (Journal of Innovative Applied Mathematics and Computational Sciences, 2024)
Differential equations are fundamental mathematical tools with wide-ranging applications in science and economics. This study delves into their role in business, focusing on strategic analysis and forecasting for profit maximization and operational efficiency in manufacturing. It explores various equation types, from ordinary to partial differentials, highlighting their critical role in modeling economic phenomena. Through a comprehensive case study, this research demonstrates the practical application of differential equations in optimizing production, sales, revenue, and profit. The study emphasizes their impact on strategic decision-making and navigating complex market dynamics for sustained growth and profitability.